The effects of bovine bone scaffold on the microscopic Biological response of human chondrocytes - Abdullah, Baharudin (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2009)
Introduction In the creation of cartilaginous tissue, the choice of suitable scaffold remains a great challenge. The current available scaffold either natural or synthetic still does not meet the requirement of a scaffold for cartilage tissue engineering. The ideal scaffold provides mechanical stability to the individual cell as a construct or transitional framework before synthesis of new extra cellular matrix. Objective The aim of this study was to produce bovine bone as a tissue engineering construct for cartilage reconstruction and to determine the effects of bovine bone on biological human chondrocyte in vitro. Method Human chondrocytes were cultured and seeded into bovine scaffold with seeding density of 1 x 105 cells per 100 ul I scaffold and incubated for 24 hours, 2 days, 5 days and 7 days. Proliferation and viability of the cells were measured by mitochondrial dehydrogenase activity (MTT assay), adhesion study was analyzed using Scanning Electron Microscopy (SEM) and differentiation study was analyzed by lmmunoflorescent staining using Confocal Laser Scanning Electron Microscopy (CLSM).